Comparative transcriptome analysis reveals the molecular mechanism of heat-tolerance in Neopyropia yezoensis induced by Sargassum horneri extract - Xing, Qikun; Han, Sol; Park, Ji-Sook; Yarish, Charles; Kim, Jang K. (Frontiers in Marine Science, 2023)
Heat stress is one of the main threats for the seaweed aquaculture, leading to the decay of the blades and causing serious economic losses. A newly developed biostimulant, Sargassum horneri extract (SHE), can enhance the heat-tolerance in Neopyropia yezoensis, which can be applied in the seaweed aquaculture. However, the molecular mechanism underlying this acquired heat-tolerance is still unclear. In this study, we examined the transcriptional regulation of N. yezoensis under heat stress after the SHE pre-treatment. Our results show that, under heat stress, the SHE pre-treatment can alleviate the suppression of genes involved in normal cell activities, such as ribosome biogenesis, photosynthesis, respiration and cell cycle. On the other hand, SHE pre-treatment can also induce some key genes involved in the heat-tolerance. We also found that the combination of SHE pre-treatment and heat stress can induce some genes related to epigenetic modification, suggesting that SHE may facilitate the formation of heat stress memory in N. yezoensis. Our study provides information for understanding the molecular mechanism of heat-tolerance in N. yezoensis and for promoting the application of seaweed-derived biostimulants in the seaweed aquaculture.